Laura Cázares Hernández, El caldero fáustico: la narrativa de Sergio Pitol. Universidad Autónoma Metropolitana-Iztapalapa, México, 2006. - Elizabeth Corral Peña (Nueva Revista de Filología Hispánica, 2008)
Se reseñó el libro: El caldero fáustico: la narrativa de Sergio Pitol.